2015
DOI: 10.1371/journal.pone.0118095
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Mycobacterium tuberculosis from Guadalajara, Mexico and Identification of a Rare Multidrug Resistant Beijing Genotype

Abstract: Determining the genetic diversity of M. tuberculosis strains allows identification of the distinct Mycobacterium tuberculosis genotypes responsible for tuberculosis in different regions. Several studies have reported the genetic diversity of M. tuberculosis strains in Mexico, but little information is available from the state of Jalisco. Therefore, the aim of this study was to determine the genetic diversity of Mycobacterium tuberculosis clinical isolates from Western Mexico. Sixty-eight M. tuberculosis isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
(46 reference statements)
2
23
0
Order By: Relevance
“…And they were identified as the causative agents of tuberculosis in the world. For each families of MTB resistance to rifampicin, the prevalence was analyzed for the selected studies as follows: Beijing nineteen studies [14, 15, 16, 17, 18, 19, 20, 21, 22, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31], LAM ten studies [15, 17, 23, 25, 28, 29, 32, 33, 34, 35], T ten studies [3, 15, 16, 17, 23, 27, 28, 32, 34, 35], EAI eight studies [18, 22, 25, 27, 28, 29, 33, 36], Ural four studies [15, 17, 30, 34] Haarlem five studies [15, 23, 25, 28, 34], CAS four studies [15, 29, 30, 35] and MANU two studies [16, 29]. The proportion of rifampicin resistance varies by the type of regions and strains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And they were identified as the causative agents of tuberculosis in the world. For each families of MTB resistance to rifampicin, the prevalence was analyzed for the selected studies as follows: Beijing nineteen studies [14, 15, 16, 17, 18, 19, 20, 21, 22, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31], LAM ten studies [15, 17, 23, 25, 28, 29, 32, 33, 34, 35], T ten studies [3, 15, 16, 17, 23, 27, 28, 32, 34, 35], EAI eight studies [18, 22, 25, 27, 28, 29, 33, 36], Ural four studies [15, 17, 30, 34] Haarlem five studies [15, 23, 25, 28, 34], CAS four studies [15, 29, 30, 35] and MANU two studies [16, 29]. The proportion of rifampicin resistance varies by the type of regions and strains.…”
Section: Resultsmentioning
confidence: 99%
“…Eigteen studies reported rifampicin resistance Beijing family. Of these studies, nine were conducted in Western Pacific Region, reported 1309 (97.68%) resistance Beijing family [2, 16, 20, 21, 22, 28, 29, 30, 31], three studies were conducted in South-East Asia Region, reported 15 (1.11%) resistance Beijing family [15, 19, 25], two studies were conducted in European Region and identified 14 (1.04%) resistance Beijing family [17, 24] and two studies were conducted in Region of American but only two resistance Beijing family [18, 23]. One study which was conducted in African Region [29] and one study conducted in Eastern-Mediterranean Region did not report a rifampicin resistance Beijing family [30].…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, whole-genome sequencing has revealed substantial genetic diversity between strains, leading to an improved phylogenetic SNP-based strain classification [28]. Studies in Peru [25,29,30], Argentina [31], Mexico [32,33], and Brazil [34,35,36,37] have all examined the genetic diversity of MTB in Latin America and have established that the predominant strains have evolved from the Euro-American lineage 4. This domination of lineage 4 in South America, alongside its worldwide distribution, supports the hypothesis that it was introduced and dispersed by European colonialists in the mid-sixteenth to nineteenth centuries, as discussed above [38,39,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Little information is available on the molecular epidemiology in Mexico of Mycobacterium species. However, the published data report a variety of lineages that are prevalent in the surveyed regions ( Lopez-Rocha et al 2013 , Vera-Cabrera et al 2014 , Flores-Treviño et al 2015 , Zenteno-Cuevas et al 2015 ). While it is clear that T2D constitutes a risk for the development of TB, the immunological abnormalities that contribute to this event and the influence of the virulence of Mtb strains are less clear.…”
Section: Discussionmentioning
confidence: 99%